Reimagining loyalty rewards programmes via blockchain: usage, loyalty, and firm performance - Hendricks, Matthew (School of Management Studies, 2025)
The emergence of blockchain technology is poised to revolutionise the loyalty programme (LP) landscape. Still, there is a dearth of research exploring the factors that influence the acceptance and resultant loyalty creation of blockchain-based LPs. This study examines the relationship between technological acceptance, loyalty creation, redemption and word-of-mouth yielded by a blockchain-based loyalty programme (BBLP). Employing the Diffusion of Innovation Theory and the Technological Acceptance Model (TAM), the study investigates the intention to use a BBLP as influenced by the perceived ease of use and usefulness of a BBLP. An integrated model combining the theories of Watson et al. (2015), Davis (1985) and Rogers (1995) was analysed in three separate but interrelated, descriptive, cross-sectional survey studies. In Study One (N = 995), the factors which influence the perceived ease of use, perceived usefulness, and ultimate intention to utilise a BBLP were examined. Study Two (N= 756) focused on the factors which contribute to the development of behavioural and attitudinal loyalty towards a BBLP, and the relationship that the intention to use a BBLP has with behavioural and attitudinal loyalty. Lastly, Study Three (N = 1157) focused on the relationship between the intention to use a BBPL and attitudinal and behavioural loyalty, as well as the relationship that behavioural and attitudinal loyalty has with word-of-mouth (WoM) and redemption. Redemption is typically neglected in the literature as a specific outcome, with only a handful of studies examining it as a specific variable. The perceived value of cryptocurrency, trust in blockchain and cryptocurrency, are emerging antecedents that are focused upon. This study is one of few that the perceived value of cryptocurrency is examined as an LP reward, which influences both PEOU and PU. The data was analysed using PLS-SEM and the software SmartPLS 4. The intention to use a BBLP and both behavioural and attitudinal loyalty were found to influence each other and enhance WoM. Attitudinal loyalty influenced redemption, though no significant link was found between behavioural loyalty and redemption. Managers should carefully consider their incentive strategies for a BBLP by incorporating relative advantage, satisfaction, trust, and commitment to drive loyalty.